Ubiquitin-specific protease 4 promotes glioblastoma multiforme via activating ERK pathway - Zhou, Yudong (Onco Targets Ther, 2019)
BACKGROUND: Glioblastoma multiforme (GBM) is one of the most common brain tumors in adults. Current treatments cannot increase survival to a large extent, as the glioblastoma development mechanisms remain unknown. It has been well documented that ubiquitination contributes to tumor initiation and/or progression in many kinds of cancer. Ubiquitin-specific protease 4 (USP4), a member of deubiquitinating enzymes (DUBs) family, can remove ubiquitin residues and play a role in cancer development. METHODS: In the current study, lentiviruses were used to manipulate the expression of USP4. Real-time PCR and Western blot were used to measure the expression level of USP4. Then, CCK-8 and annexin-V staining were used to detect cell proliferation and cell apoptosis, respectively. RESULTS: First, we found that USP4 was highly upregulated in GBM tissues in comparison with that in normal tissues and high level of USP4 correlated with poor prognosis. Moreover, knockdown of USP4 could significantly inhibit cell proliferation and increase cell apoptosis in U87 and T98G cells. Cells with stable USP4 reduction exhibited slower tumor growth rate and smaller tumor size than the control group cells in a xenograft mouse model. Inhibition of USP4 downregulated the expression of PCNA, Bcl-2 and p-ERK1/2, but upregulated the expression of Bax both in vitro and in vivo. Inversely, USP4 overexpression could attenuate the effects contributed by ERK inhibitor. TGF-βR inhibition reduced level of TGF-βR1, p-smad2 and p-ERK1/2 which can partially be rescued by USP4 overexpression. CONCLUSION: USP4, as a potential novel oncogene, promotes GBM by activation of ERK pathway through regulating TGF-β.